2017
DOI: 10.15560/13.4.261
|View full text |Cite
|
Sign up to set email alerts
|

The Largetooth Sawfish, Pristis pristis (Linnaeus, 1758), is not extirpated from Peru: new records from Tumbes

Abstract: The Largetooth Sawfish, Pristis pristis, was for a long time considered extirpated from Peru. However, here we report the capture of 2 individuals from the north coast of Peru, indicating that this species is still extant in Peruvian waters. Both individuals were adult-sized and their encounters occurred during the austral summer, which could indicate a seasonal presence in those waters. Gillnets are still a major threat for the species as both specimens were incidentally captured with this gear. Our finding h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…At a regional scale, part of the Central American countries were considered as PU (Dulvy et al 2016); however, recent records from this study confirm the presence of the largetooth sawfish in Costa Rica, which is now part of the extant distribution of both the Eastern Pacific and Western Atlantic populations (Faria et al 2013). Similarly, studies from 2017 and 2018 in data-poor re gions (Mendoza et al 2017, White et al 2017, Leeney et al 2018 have demonstrated the persistence of the species where it was thought to be extinct or PU. This shows that there are other beacons of hope outside of Australian pro-tected areas where sawfish are found more frequently than any other country in their historical range.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…At a regional scale, part of the Central American countries were considered as PU (Dulvy et al 2016); however, recent records from this study confirm the presence of the largetooth sawfish in Costa Rica, which is now part of the extant distribution of both the Eastern Pacific and Western Atlantic populations (Faria et al 2013). Similarly, studies from 2017 and 2018 in data-poor re gions (Mendoza et al 2017, White et al 2017, Leeney et al 2018 have demonstrated the persistence of the species where it was thought to be extinct or PU. This shows that there are other beacons of hope outside of Australian pro-tected areas where sawfish are found more frequently than any other country in their historical range.…”
Section: Discussionmentioning
confidence: 53%
“…The WA and EP subpopulations occurred in coastal and freshwater ecosystems of countries in Latin America (Cook et al 2005, Faria et al 2013. However, according to recent studies, populations of largetooth sawfish have been decimated from México (Bonfil et al 2017), Peru (Mendoza et al 2017), Colombia and Venezuela (Gómez-Rodríguez et al 2014). In some countries of Central America, knowledge about its current distribution remains uncertain due to the lack of studies and/or recent sightings (Dulvy et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although the large-tooth sawfish (Pristis pristis) might still inhabit tropical waters of northern Peru (DULVY et al, 2014;MENDOZA et al, 2017), and the fossil record of pristids from the East Pisco Basin spans from the middle Eocene to the late Miocene, sawfishes are currently absent from the cool, upwelling-influenced coastal waters of present-day southern Peru -an observation that might suggest warmer-than-today seawater temperatures for the Lutetian nearshore environments of southern Peru. This interpretation fits perfectly the global climatic scenario of the middle Eocene, which was characterized by high temperatures worldwide (e.g., ZACHOS et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…No recent biological or ecological information exists for P. pristis in Colombia and Panama, since it is an extremely rare species in the area, therefore difficult to assess and research. The species is known to be locally extinct in 27 of the 75 countries where it was historically present (Faria et al 2013, Dulvy et al 2016, Mendoza et al 2017. In its native Caribbean range, P. pristis is thought to be locally extinct (Gómez-Rodríguez et al 2014).…”
Section: Introductionmentioning
confidence: 99%